Electric resistence hysteresis of platinum filament in chilled air/hydrogen mixtures - Каlіnchak V. V.; Chernenko , O. S.; Fedorenko, A. V. (Physics and Chemistry of Solid State, 2020)
Ignition of gaseous combustible mixtures on catalytically active hot solid surfaces has numerous applications in many industrial processes and is a complex process that involves close interaction between surface processes and transfer processes in the gas mixture. In this paper, stable and critical states catalytic oxidation of hydrogen impurities in air on a platinum filament are considered. It is shown that filament temperature and its resistance depending on the mixture temperature and hydrogen concentration are of the hysteresis features. Within this hysteresis region, it is possible to achieve the catalytic combustion mode of hydrogen as a result preheating the catalyst filament above a certain critical value. The dependence of the limiting hydrogen's concentration on catalyst filament's diameter, above which is observed in the cold gas mixture self-sustaining catalytic combustion without electric current.